You are on page 1of 11

ID : in-10-Trigonometry [1]

Class 10
Trigonometry
For more such worksheets visit www.edugain.com

Answer the questions

(1) Simplify

tan2β
(2) Simplify 1 + .
1 + secβ

(3) Simplify

(4) If cosec θ = a/b and 0° > θ > 90°, find value of cot θ.

(5) Simplify

(6) Simplify 3(sin4θ + cos 4θ) - 2(sin6θ + cos 6θ)


(7) A rope is tightly stretched and attached from top of a vertical tower to the ground. The angle made by
rope with ground is 30°. If height of the tower is m, find length of the rope.

7 sinθ - cosθ
(8) If 7 tanθ = 4, find the value of .
7 sinθ + cosθ

(9) If AB = and AC = , find value of (sin A × tan A).

(10) If 2sinθ – cosθ = 2, find the value of sinθ + 2cosθ.

(11) If tan θ + cot θ = 5, find the value of tan 2 θ + cot 2 θ.

(12) Simplify

(13) Simplify (1 + cotθ + cosecθ) (1 + tanθ - secθ)

Copyright 2017 www.edugain.com Personal use only. Commercial use is strictly prohibited.
ID : in-10-Trigonometry [2]

Choose correct answer(s) from the given choices

(14) =?

2 2
a. b.
2 sin 2θ - 1 1 - sin 2θ

2 2
c. d.
1 - cos 2θ 1 - 2 sin 2θ

Check True/False

(15) tan 8° - cot 8° < 0


True False

© 2017 Edugain (www.edugain.com). Many more such worksheets can be


All Rights Reserved generated at www.edugain.com

Copyright 2017 www.edugain.com Personal use only. Commercial use is strictly prohibited.
ID : in-10-Trigonometry [3]

Answers
(1) 0

Step 1
On combining two fractions
=

Step 2

Since sin2θ + cos 2θ + = 1


=

(2) sec β

Step 1

tan2β
Let, S = 1 +
1 + secβ

Step 2

Using identity tan2θ = sec 2θ - 1,


sec2β - 1
⇒S=1+
1 + secβ

Step 3

Using a 2 - b 2 = (a+b)(a-b),
(secβ + 1)(secβ - 1)
⇒S=1+
1 + secβ
⇒ S = 1 + (secβ - 1)
⇒ S = secβ

Copyright 2017 www.edugain.com Personal use only. Commercial use is strictly prohibited.
ID : in-10-Trigonometry [4]

(3) sin2θ cos 2θ

Step 1
(1 + cotθ + tanθ)(sinθ - cosθ)
We have been asked to simplify the .
sec3θ - cosec 3θ

Step 2

cosθ sinθ
(1 + cotθ + tanθ)(sinθ - cosθ) (1 + + )(sinθ - cosθ)
= sinθ cosθ ) [Since,
sec3θ - cosec 3θ
(secθ - cosecθ)(sec 2θ + secθ × cosecθ + cosec 2θ)
a3 - b 3 = (a - b)(a2 + ab + b 2]

sinθ cosθ + cos2θ + sin 2θ


( )(sinθ - cosθ)
sinθ cosθ 1
= [Since, secθ = and cosecθ =
1 1 1 1 1 cosθ
( - )( + + )
cosθ sinθ cos2θ sinθ cosθ cos2θ

1
]
sinθ

1 + sinθ cosθ
( )(sinθ - cosθ)
sinθ cosθ
=
(sinθ - cosθ)(sin 2θ + sinθ cosθ + cos2θ)

(sinθ cosθ)(sin 2θ cos 2θ)

(1 + sinθ cosθ)(sinθ - cosθ)(sin3θ cos 3θ)


=
(sinθ cosθ)(sinθ - cosθ)(1 + sinθ cosθ)
= sin2θ cos 2θ

Step 3
(1 + cotθ + tanθ)(sinθ - cosθ)
Therefore, is equal to the sin2θ cos 2θ.
sec3θ - cosec 3θ

Copyright 2017 www.edugain.com Personal use only. Commercial use is strictly prohibited.
ID : in-10-Trigonometry [5]

(4)

Step 1
We know that,
cot θ = √(cosec 2θ - 1)

Step 2
Now replace value of cosec(θ) in above equation
⇒ cot(θ) =

Step 3
Simplify RHS of above equation

⇒ cot(θ) =

(5) 2 tanθ

Step 1

Step 2

Step 3

Copyright 2017 www.edugain.com Personal use only. Commercial use is strictly prohibited.
ID : in-10-Trigonometry [6]
(6) 1

Step 1

= 3 (sin 4θ + cos 4θ) - 2 [ (sin 2θ)3 + (cos2θ)3 } ]

Step 2

= 3 (sin 4θ + cos 4θ) - 2 [ (sin 2θ + cos 2θ) {(sin2θ)2 + (cos2θ)2 - sin2θ cos 2θ } ]

Step 3

Since sin2θ + cos 2θ = 1


=3 (sin4θ + cos 4θ) - 2 {sin 4θ + cos 4θ - sin 2θ cos 2θ }

Step 4

= sin4θ + cos 4θ + 2 sin 2θ cos 2θ

Step 5

= (sin 2θ + cos 2θ)2 = 12 = 1

(7) m

Step 1
In following figure, AC shows the towerm BC is the rope connected from ground to tower, and
angle ∠B is the angle angle made by rope with ground.

Step 2
AC/BC = sin(∠B)
⇒ AC/BC = sin(30°)

Copyright 2017 www.edugain.com Personal use only. Commercial use is strictly prohibited.
ID : in-10-Trigonometry [7]
(8) 3/5

Step 1
Lets
7 sinθ - cosθ
S=
7 sinθ + cosθ

Step 2
Now divide numerator and denominator of this fraction by cosθ
(7 sinθ - cosθ)/cosθ
⇒S=
(7 sinθ + cosθ)/cosθ
(7 sinθ/cosθ - 1)
⇒S=
(7 sinθ/cosθ + 1)
(7 tanθ - 1)
⇒S=
(7 tabθ + 1)

Step 3
Now replace 7 tanθ with is value (7 tanθ = 4)
(4 - 1)
⇒S=
(4 + 1)
⇒ S = 3/5

(9)

Step 1

Step 2
BC =

Step 3
sin A × tan A = (BC/AC) × (BC/AB) =

Copyright 2017 www.edugain.com Personal use only. Commercial use is strictly prohibited.
ID : in-10-Trigonometry [8]
(10) 1

Step 1
It is given that
2sinθ – cosθ = 2
⇒ (2sinθ – cosθ)2 = 22 ....... [On squaring both sides]

Step 2

Now add (sinθ + 2cosθ)2 to both sides of equation


⇒ (2sinθ – cosθ)2 + (sinθ + 2cosθ)2 = 22 + (sinθ + 2cosθ)2
⇒ 4sin2θ + cos 2θ - 4sinθcosθ + sin 2θ + 4cos 2θ + 4sinθcosθ = 4 + (sinθ + 2cosθ) 2
⇒ 5sin2θ + 5cos 2θ + 4sinθcosθ - 4sinθcosθ = 4 + (sinθ + 2cosθ) 2
⇒ 5(sin2θ + cos 2θ) = 4 + (sinθ + 2cosθ) 2
⇒ 5 = 4 + (sinθ + 2cosθ) 2
⇒ (sinθ + 2cosθ)2 = 5 - 4
⇒ (sinθ + 2cosθ)2 = 1
⇒ sinθ + 2cosθ = ± 1

Step 3
Since 2sinθ – cosθ=2, ignore the negative value.
Therefore, sinθ + 2cosθ = 1

(11) 23

Step 1
tan θ + cot θ = 5

Step 2
On squaring both sides,
(tan θ + cot θ) 2 = 52

Step 3

tan2θ + cot 2θ + 2 tanθ cotθ = 25

Step 4

tan2θ + cot 2θ + 2 = 25

Step 5

tan2θ + cot 2θ = 25 - 2 = 23

Copyright 2017 www.edugain.com Personal use only. Commercial use is strictly prohibited.
ID : in-10-Trigonometry [9]
(12) 0

Step 1
On adding two fractions

Step 2

Step 3

Step 4

Copyright 2017 www.edugain.com Personal use only. Commercial use is strictly prohibited.
ID : in-10-Trigonometry [10]
(13) 2

Step 1
We need to find following product
S = (1 + cotθ + cosecθ) (1 + tanθ - secθ)

Step 2
On multiplying each terms
⇒ S = 1 (1 + tanθ - secθ) + cotθ (1 + tanθ - secθ) + cosecθ (1 + tanθ - secθ)
⇒ S = (1 + tanθ - secθ) + (cotθ + cotθ tanθ - cotθ secθ ) + (cosecθ + cosecθ tanθ - cosecθ secθ)

Step 3
Using identities cotθ tanθ = 1, cotθ secθ = cosecθ and cosecθ tanθ = secθ
⇒ S = (1 + tanθ - secθ) + (cotθ + 1 - cosecθ ) + (cosecθ + secθ - cosecθ secθ)

Step 4
Now positive cosecθ and secθ will cancel each other
⇒ S = (1 + tanθ - secθ) + (cotθ + 1 - cosecθ ) + (cosecθ + secθ - cosecθ secθ)
⇒ S = 2 + tanθ + cotθ - cosecθ secθ

Step 5
Using identities tanθ = sinθ/cosθ, and cotθ = cosθ/sinθ
sinθ cosθ
⇒S=2+ + - cosecθ secθ
cosθ sinθ

sin2θ + cos 2θ
⇒S=2+ - cosecθ secθ
sinθcosθ
1
⇒S=2+ - cosecθ secθ
sinθcosθ
⇒ S = 2 + cosecθ secθ - cosecθ secθ
⇒S=2

Copyright 2017 www.edugain.com Personal use only. Commercial use is strictly prohibited.
ID : in-10-Trigonometry [11]

2
(14) a.
2 sin 2θ - 1

Step 1
On adding two fractions,
S=

Step 2
Let,

⇒S=

⇒S=

Step 3

Using identity sin2θ + cos 2θ = 1

,⇒S=

⇒S=

⇒S=

⇒S=

(15) True

We know that cotθ is greater than tanθ, if θ < 45°.


Therefore tan 8° - cot 8° will be negative, and statement "tan 8° - cot 8° < 0" is True.

Copyright 2017 www.edugain.com Personal use only. Commercial use is strictly prohibited.